Implementasi Nilai-nilai Islam dalam Manajemen Laba Efisien Perbankan Syariah di Indonesia - M. Wahyuddin Abdullah; Nurul Ainun (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
This study aims to determine the earnings management efficient practices and compliance with the value of Islam on sharia banking in Indonesia. The research is mixed method and data used in the form of secondary data obtained from the annual report and the report sustanability sharia banking with the observation period 2012 to 2015. The variables used were proxies of earning management (PML) and the future profitability (PMD). This research employs the model analysis by using ordinal logistic regression. The results show that the PML effect on PMD, sharia banking practice efficient earnings management. Three of the five sharia banks do efficient earnings management practices on regular basis during the period of observation, that BRI Syaria, BSM, and BNI Syaria. The Three shariah banks obtain efficient earnings through the principals of management practices in Islamic values, namely:maslahah, honesty, and fairness.